Inactivation of Cerebral Cavernous Malformation Genes Results in Accumulation of von Willebrand Factor and Redistribution of Weibel-Palade Bodies in Endothelial Cells - Much, Christiane D.; Sendtner, Barbara S.; Schwefel, Konrad; Freund, Eric; Bekeschus, Sander; Otto, Oliver; Pagenstecher, Axel; Felbor, Ute; Rath, Matthias; Spiegler, Stefanie (Frontiers in Molecular Biosciences, 2021)
Cerebral cavernous malformations are slow-flow thrombi-containing vessels induced by two-step inactivation of the CCM1, CCM2 or CCM3 gene within endothelial cells. They predispose to intracerebral bleedings and focal neurological deficits. Our understanding of the cellular and molecular mechanisms that trigger endothelial dysfunction in cavernous malformations is still incomplete. To model both, hereditary and sporadic CCM disease, blood outgrowth endothelial cells (BOECs) with a heterozygous CCM1 germline mutation and immortalized wild-type human umbilical vein endothelial cells were subjected to CRISPR/Cas9-mediated CCM1 gene disruption. CCM1-/- BOECs demonstrated alterations in cell morphology, actin cytoskeleton dynamics, tube formation, and expression of the transcription factors KLF2 and KLF4. Furthermore, high VWF immunoreactivity was observed in CCM1-/- BOECs, in immortalized umbilical vein endothelial cells upon CRISPR/Cas9-induced inactivation of either CCM1, CCM2 or CCM3 as well as in CCM tissue samples of familial cases. Observer-independent high-content imaging revealed a striking reduction of perinuclear Weibel-Palade bodies in unstimulated CCM1-/- BOECs which was observed in CCM1+/- BOECs only after stimulation with PMA or histamine. Our results demonstrate that CRISPR/Cas9 genome editing is a powerful tool to model different aspects of CCM disease in vitro and that CCM1 inactivation induces high-level expression of VWF and redistribution of Weibel-Palade bodies within endothelial cells.